APLIKASI PELAPORAN KEGIATAN MENTORING DI UNIVERSITAS TEKNOLOGI SUMBAWA BERBASIS ANDROID - Nawassyarif; Yahya Abdan Syakura; Nurlaily (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
Sumbawa University of Technology (UTS) is a private university in the Sumbawa Regency, West Nusa Tenggara Province. The Mentoring Unit is one of the organizations located at the Sumbawa University of Technology. This research aims to build an Android-based mentoring activity reporting application that can be used to assist the reporting process of mentoring activities which includes attendance, recitation assessment, and examination evaluation, and also administrators in managing activities so that they can run well. Researchers built an Androidbased application and developed it using Android Studio by using MySql as a database and sublime text as a text editor. Software development method uses Waterfall Model and software testing is done through black-box testing. Data collection techniques in research using interviews and documentation, the results of this study are web-based thesis registration applications that are useful to assist teachers in the process of mentoring and management in managing activities in order to run well